Simplification of MIMO Dynamic Systems using Differentiation and Cauer Second Form - CB, Vishwakarma (International Journal of Computer Sciences and Engineering, 2019)
A simplification method for multi-inputs and multi-outputs (MIMO) dynamic system via reducing the order of the original large-scale system is presented in this paper. The common denominator of the original system is reduced by using differentiation method while the numerator coefficients are obtained by applying Cauer second form. The proposed method is computationally simple and capable to retain the properties of the original system. The viability of the proposed method has been checked via one numerical example.